Perbandingan Hukum Keluarga Islam di Arab Saudi, Indonesia, Turki, dan Iran: Perspektif, Implementasi, Dan Dampaknya - Novri Hanafiah; Syarifuddin; Ali Murtadho (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Islamic Family Law is an integral part of the lives of Muslim communities around the world. Although the fundamental principles of Islamic family law are derived from the Qur'an and Hadith, its implementation can vary across different countries or regions. This article aims to discuss a comparative overview of family law in several Muslim-majority countries that represent diverse legal systems, such as Saudi Arabia, Indonesia, Turkey, and Iran. Through a descriptive approach, this article analyzes the differences and similarities in the application of Islamic family law in these countries, focusing on issues such as marriage, polygamy, divorce, and inheritance. The findings show that despite shared foundational principles, local cultural, social, and political factors influence the different implementations of Islamic family law in each country.